Penerapan Konsep Branding Dan Digitalisasi Pada Hasil Produk Pertanian Di Dusun Gunung Malang, Desa Sukomakmur, Kabupaten Magelang - Muhammad Nugroho Aji Prabowo; Devan Rafy Ramadhan; Laurensius Wemalio Yustirio; Adhitya Candra Pratama; Syifaul Jinan; Nabila Hidayatul Lail; Rachel Ika Faudina; Dini Al Maunah; Nabilah Hanan Kurnia Putri; Ristiana Dwi Widyanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Implementation of Branding and Digitalization Concepts for Agricultural Products in Gunung Malang Hamlet, Sukomakmur Village, Magelang Regency. Advances in digital technology have brought convenience to various aspects of life, including marketing, which can now be done simply through mobile phones. Platforms such as Instagram, TikTok, and Facebook serve not only as social media but also as online marketplaces without the constraints of time, space, and distance. However, MSMEs in Gunung Malang Hamlet still face obstacles in implementing branding and digital marketing, including product labeling and packaging that do not reflect local wisdom in an attractive manner. Therefore, this Community Service Program (KKN) program presents socialization as a sociological approach through the collection of data through direct observation of MSMEs in Gunung Malang Hamlet. This activity aims to increase MSMEs' understanding and awareness of the importance of digital marketing and labeling in product packaging. With increasingly fierce market competition, branding and packaging design, as part of an online marketing strategy, are considered more relevant to the needs of MSMEs. This will strengthen MSME products in the competitive market by utilizing local wisdom.